2017
DOI: 10.1684/epd.2017.0923
|View full text |Cite
|
Sign up to set email alerts
|

Transient lesions of the splenium of the corpus callosum following rapid withdrawal of levetiracetam

Abstract: Transient lesions of the splenium of the corpus callosum are characterized by MRI findings. The lesions are very rare, but significant from a clinical standpoint as differential diagnoses include serious conditions such as encephalitis, meningitis, and neuroleptic malignant syndrome. In addition, it is reported that some are attributed to the withdrawal of antiepileptic drugs. Here, we present a case of transient lesions of the splenium of the corpus callosum following rapid withdrawal of levetiracetam alone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…1. Axial diffusion-weighted magnetic resonance images (DWI) demonstrate high signal intensity on the sple nium of the corpus callosum on day 2 of hospitalization diverse clinical conditions including the use of antiepileptic drugs, hypoglycaemia, and are related to migraine with aura in children (10)(11)(12). Recent case reports illustrate that rotavirus RNA may be found in the cerebrospinal fluid (CSF) of patients with gastroenteritis and neurological symptoms (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…1. Axial diffusion-weighted magnetic resonance images (DWI) demonstrate high signal intensity on the sple nium of the corpus callosum on day 2 of hospitalization diverse clinical conditions including the use of antiepileptic drugs, hypoglycaemia, and are related to migraine with aura in children (10)(11)(12). Recent case reports illustrate that rotavirus RNA may be found in the cerebrospinal fluid (CSF) of patients with gastroenteritis and neurological symptoms (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam was suspected to play a role in the onset of RESLES in case 7, to the best of our knowledge, this is the first report of levetiracetam to be associated with the etiology of RESLES, while the withdrawal of levetiracetam has been previously reported to cause RESLES (34). After carbamazepine treatment was given because of vestibular paroxysmia in case 12, an SCC lesion was discovered 34 days later after carbamazepine treatment.…”
Section: Discussionmentioning
confidence: 65%
“…Valproate (26), oxcarbazepine (5,33), topiramate (30), levetiracetam (34), phenytoin (3,42), carbamazepine (72) Oxcarbazepine (33) Autoimmune disease…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ­antiepileptic drugs can reportedly cause CLOCCs; for ­example, carbamazepine can interact with arginine-­vasopressin and therein influence fluid balance systems [7, 8]. However, only 1 CLOCC case has been reported that was caused by rapid withdrawal of levetiracetam, which is primarily used as a perioperative antiepileptic drug in our study [9]. This prejudicial drug usage might affect the result and thus we could not identify the correlation between antiepileptic drugs and CLOCCs in SAH patients.…”
Section: Discussion/conclusionmentioning
confidence: 85%